The Empowerment and Independence of Assisted Village, Bagan Kuala Through Various Community Services on Ecotourism, Ecoprint Development, Waste Management, and Malaria Eradication: Pemberdayaan dan Kemandirian Desa Binaan Bagan Kuala Melalui Berbagai Inisiatif Masyarakat yang Berfokus Pada Ekowisata, Pengembangan Ecoprint, Pengelolaan Sampah, dan Pemberantasan Malaria - Basyuni, Mohammad; Mubaraq, Alfian Mubaraq; Slamet, Bejo Slamet; Rangkuti, Ahmad Baiquni; Jumilawaty, Erni Jumilawaty; Elfiati, Deni Elfiati; Risnasari, Iwan Risnasari; Aznawi, Andi Aznan; Sivaipram, Itchika Sivaipram; Nauly, Meutia Nauly; Siregar, Ameilia Zuliyanti; Arrasyid, Nurfida Khairina; Ritarwan, Kiking Ritarwan; Susilowati, Arida Susilowati; Delvian, Delvian; Siregar, Etti Sartina; Hanafiah, Diana Sofia (Institut Riset dan Publikasi Indonesia, 2025)
This community service examines the empowerment and independence of Desa Binaan Bagan Kuala in the Tanjung Beringin Sub-district of Serdang Bedagai Regency, North Sumatra, through the implementation of ecotourism, ecoprint development activities, appropriate waste management, and malaria eradication initiatives. The objectives of this research are to assess the socio-economic impacts of these initiatives on the local community and evaluate their contributions to sustainable development. The research utilized a mixed-methods approach, collecting both qualitative and quantitative data from 150 households in the village through surveys and interviews. The findings indicate that ecotourism initiatives have generated a 30% increase in local income, attracting over 1,000 visitors annually and creating approximately 50 jobs. The ecoprint development activities have empowered 40 local artisans, resulting in a 25% increase in their income and the production of over 2,000 ecoprint items in the past year. Moreover, the implementation of appropriate waste management practices has led to a 40% reduction in local waste pollution, with 75% of households participating in waste segregation and recycling programs. Malaria eradication efforts have also shown significant results, with reported malaria cases decreasing by 60% over the last two years due to community engagement in health education and the distribution of insecticide-treated nets. This comprehensive approach to community empowerment not only enhances economic independence but also promotes environmental sustainability and public health. The success of these initiatives demonstrates the potential for rural communities in Indonesia to achieve sustainable development through participatory strategies that address both economic and health-related challenges.